PENGARUH TRANSPORTASI OJEK ONLINE TERHADAP PENDAPATAN TAKSI KOTA DI KOTA SAMARINDA - Mihani; Riduansah (Tinta Nusantara 2018 Vol.1, 2022)
The purpose of this study was to determine how the effect of online motorcycle taxi transportation on city taxi revenues in the city of Samarinda. This study uses one independent variable, namely online motorcycle taxi transportation with one dependent variable, namely city taxi revenue. The data in this study were collected by distributing questionnaires to 60 city taxi drivers as research samples. The data analysis methods used are Validity Test, Reliability Test, Normality Test, Linearity Test, t-test, Determination Test, Simple Linear Regression Test. Based on data analysis, the results showed that the value of the constant coefficient of 23,442 and the value of the regression coefficient of the transportation variable was 0.395 with a positive direction. Then the t test value is known to be sig. of 0.000 < 0.05. The results of the determination test obtained a value of 0.232 or 23.3%. This means that the online motorcycle taxi transportation variable has a fairly effective effect on city taxi revenues in the city of Samarinda.